2008
DOI: 10.1002/adma.200800533
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Conjugated Polyelectrolytes in Optoelectronic Devices

Abstract: Conjugated polyelectrolytes comprise an electronically delocalized backbone with pendant groups bearing ionic functionalities. Important new developments regarding their use to improve charge injection from metallic electrodes into organic semiconductors, a key requirement in emissive devices, have recently appeared. This article provides an overview of recent studies concerning the basic properties of conjugated polyelectrolytes as a function of molecular structure, and of optoelectronic devices with conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
345
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(349 citation statements)
references
References 174 publications
2
345
0
2
Order By: Relevance
“…The devices showed very short response times (∼10 μs; Figure 2). This is the shortest response time reported for organic light-emitting diodes (OLEDs) with CPE injection layers 8 and is comparable to the response times of OLEDs with metal electrodes. [23][24][25] The short response times strongly indicate that long-range ion motion does not play a major role in the charge injection process.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The devices showed very short response times (∼10 μs; Figure 2). This is the shortest response time reported for organic light-emitting diodes (OLEDs) with CPE injection layers 8 and is comparable to the response times of OLEDs with metal electrodes. [23][24][25] The short response times strongly indicate that long-range ion motion does not play a major role in the charge injection process.…”
mentioning
confidence: 61%
“…[6][7][8][9][10][11][12] A range of CPEs with different counterions (anion/cation) and backbones 13,14 have been synthesized in attempts to understand the role of the ions in the charge injection process. 15,16 The promising electronic properties of CPEs in combination with their solubility in polar solvents offer a unique route to the realization of high-performance polymer light-emitting diodes (PLEDs) without the use of reactive Ca or Ba cathodes.…”
mentioning
confidence: 99%
“…In the case of inorganic metal/semiconductor contacts , to take into account the interface states, Bardeen proposed a model, where a large density of surface states induces a pining effect of the Fermi level and the presenc e at the interface of a barrier independent of the metal work function. the devices is often modulated by a dipole ( formation at the interface, it is admitted that this difference provides a hole collection barrier in OPV cells [23]. It has been already shown that the presence of such a barrier induces the presence of the kink effect in the J-V characteristics (Figure 1) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other transition metal oxide (WO 3 , V 2 O 5 , NiO) have been probed as efficient ABL. Although such interface improvement has been often carried out [8,[23][24][25][26], the operation mechanism of these ABL is still in debate. The typical values which characterize the properties of the MoO 3 are: The work function, MoO3 , the top of the valence band, VB, which is the ionisation potential, IP, the bottom of the conduction band, BC, which is the electronic affinity (EA).…”
Section: Discussionmentioning
confidence: 99%
“…A romatic conjugated polymers have semi-conducting and luminescent properties, which can be utilized in organic light-emitting diodes, organic field-effect transistors, photovoltaic cells, and chemical biosensors [1][2][3][4][5][6][7][8] . Such conjugated polymers can fluoresce various colours in the visible region through changing the conjugated backbones.…”
mentioning
confidence: 99%